2002
DOI: 10.1056/nejmoa020932
|View full text |Cite
|
Sign up to set email alerts
|

Public Use of Automated External Defibrillators

Abstract: Automated external defibrillators deployed in readily accessible, well-marked public areas in Chicago airports were used effectively to assist patients with cardiac arrest. In the cases of survivors, most of the users had no duty to act and no prior training in the use of these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
290
0
45

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 730 publications
(340 citation statements)
references
References 32 publications
5
290
0
45
Order By: Relevance
“…Advantages of this approach include the provision of “willing and trained bystanders” who are prepared and equipped with onsite AEDs to act in a cardiac arrest emergency. Successful targeted AED programs have been reported in busy airports, casinos, sports arenas, and railway stations 19, 20, 21, 29, 30. This Sao Paulo Metro targeted AED program achieved similar survival rates with intact neurological function as those observed with such programs in the United States, Europe, and Japan (Table 5).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Advantages of this approach include the provision of “willing and trained bystanders” who are prepared and equipped with onsite AEDs to act in a cardiac arrest emergency. Successful targeted AED programs have been reported in busy airports, casinos, sports arenas, and railway stations 19, 20, 21, 29, 30. This Sao Paulo Metro targeted AED program achieved similar survival rates with intact neurological function as those observed with such programs in the United States, Europe, and Japan (Table 5).…”
Section: Discussionmentioning
confidence: 66%
“…Targeted AED programs for airports, casinos, railway stations, and sports venues in the United States, Europe, and Japan have shown similar positive results, but this is the first report of such a successful program in a large Latin American city 19, 20, 21, 29, 30…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, it is often difficult to shorten the time from the cardiac arrest to the defibrillation utilizing the emergency medical service. An automated external defibrillator (AED) allows bystander rescuers to defibrillate out‐of‐hospital ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) before the emergency medical service arrives 17, 18, 19, 20, 21, 22, 23, 24, 25. In fact, nationwide dissemination of publicly accessible AEDs in Japan resulted in an earlier administration of shocks by bystanders and has improved the rate of survival 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide rapid access to defibrillation, PAD programs have been established to provide access to defibrillators in high‐use public areas. Studies show that PAD programs in railways, casinos, and airports in the United States, Europe, and Japan have improved survival in patients with OHCA 3, 4, 5, 6, 7. Despite this, a study showed that PAD was deployed successfully in less than 2% of OHCA, suggesting that there are still areas that can improve their access and deployment of PAD 8.…”
Section: Introductionmentioning
confidence: 99%